Impact of foreign direct investment on the economic growth of Lao PDR: https://doi.org/10.69692/SUJMRD0902378 - XIONGTOUA, Tongvang; CHANTHAVONE, Thongphanh; CHITTAPHONE, Namfonh; KEODUANGKHAM, Phavone; PHANTHOUAMATH, Chaleuk (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This paper aims to study impact of foreign direct investment on the economic growth of Lao PDR, with the variable of foreign direct investment in the agricultural sector (FIA), the industrial sector (FII) and the service sector (FIS) and the dependent variable that is the economic growth of Lao PDR (GDP), as a time series from 1991-2020, focusing on the analysis using the multiple regression model with the ordinary least squares method, the effect of investment on economic growth in the short-run by the method of Granger causality and the effect of investment on long-run economic growth with Johansen's cointegration method: The results of the analysis in the regression model show that the foreign direct investment in the agricultural sector is accepted null hypothesis that means, it has no effect on the economic growth of Lao PDR, the foreign direct investment in the industrial sector (FII) and the service sector (FIS) the test results reject null hypothesis with significance of 0.05, indicating that the investment results in both sectors have an effect on the economic growth of Lao PDR. The results of the analysis of foreign direct investment to the economic growth in the short-run shows that the coefficient of the foreign direct investment in service sector has a positive value and rejected null hypothesis (H0) with significance of 0.05 indicating that there is a short-run effect on the economic growth. For foreign direct investment in the agricultural and industrial sectors, there is no effect on the short-run economic growth of the Lao PDR because the null hypothesis (H0) is accepted. The results of foreign direct investment to the economic growth in the long-run shows that the coefficient of foreign direct investment in the agricultural sector has a negative value, indicating that there is no effect on the economic growth in the long-run, for the coefficient of foreign direct investment in the industrial and service sectors were a positive value and rejected null hypothesis (H0) with significance of 0.05, when there is an increase in investment in those two sectors, it will result in a long-run effect on the economy (GDP) to grow.